INNV-27. BT-LIFE (BRAIN TUMOURS, LIFESTYLE INTERVENTIONS, AND FATIGUE EVALUATION): LESSONS LEARNED FROM RUNNING A NOVEL MULTI-SECTORAL RESEARCH TRIAL. (9th November 2020) - G Rooney, Alasdair; Hewins, William; Walker, Amie; Withington, Lisa; Mackinnon, Mairi; Robson, Sara; Green, Aimee; Anderson, Garry; Bulbeck, Helen; Torrens, Claire; Emerson, Julie; Dunlop, Jo; et al.
Abstract: BACKGROUND: BT-LIFE is a multi-centre RCT of novel lifestyle coaching treatments for fatigued brain tumour patients. To our knowledge it is also the first example of 'multi-sectoral research' to combine healthcare, private, and charity sectors in this population. To maximise learning, the trial team devised a structured reflection opportunity to ask, "What went well and what would we do differently next time?" METHOD: After trial closedown we convened a six-hour 'focus group' for management, principle investigators, research assistants, interventionists, qualitative researchers, trial statisticians, and the funder. Discussion was structured using a 'timeline' wall-chart which attendees freely populated with post-it notes summarising learning points from the trial. Minutes were taken in duplicate. RESULTS: In total n=19 team members contributed. Many points were study-specific and will be used internally to plan a larger trial. Among points of wider interest, examples of success included: using regular teleconferences to co-ordinate a cohesive and highly collaborative team; obtaining secure nhs.net email addresses to facilitate multi-sectoral communication; and the clear value of employing one part-time research assistant per centre instead of relying on busy clinical staff to recruit. General future learning points included: speak to the prospective sponsor and ethical committees when writing the grant application to avoid pitfalls and facilitate faster opening if funding is secured; consider preceding emails with a phone call to 'lay the ground' in time-sensitive situations; identify staff training requirements as early as possible and cascade aggressively; and be sensitive to the fact that inter-sectoral attitudes and practices may vary widely and need actively monitored and managed. Therefore frequent and secure communication, pro-active problem-spotting, and inter-sectoral value alignment appear critical for success. CONCLUSION: BT-LIFE provides many useful lessons for anyone interested in running multi-sectoral research.